Age-related changes in the acoustic startle reflex in Fischer 344 and Long Evans rats - Rybalko, Natalia; Bureš, Zbyněk; Burianová, Jana; Popelář, Jiří; Poon, Paul W F; Syka, Josef (Experimental gerontology, 2012)
The behavioral consequences of age-related changes in the auditory system were studied in Fischer 344 (F344) rats as a model of fast aging and in Long Evans (LE) rats as a model of normal aging. Hearing thresholds, the strength of the acoustic startle responses (ASRs) to noise and tonal stimuli, and the efficiency of the prepulse inhibition (PPI) of ASR were assessed in young-adult, middle-aged, and aged rats of both strains. Compared with LE rats, F344 rats showed larger age-related hearing threshold shifts, and the amplitudes of their startle responses were mostly lower. Both rat strains demonstrated a significant decrease of startle reactivity during aging. For tonal stimuli, this decrease occurred at an earlier age in the F344 rats: middle-aged F344 animals expressed similar startle reactivity as aged F344 animals, whereas middle-aged LE animals had similar startle reactivity as young-adult LE animals. For noise stimuli, on the other hand, a similar progression of age-related ASR changes was found in both strains. No significant relationship between the hearing thresholds and the ASR amplitudes was found within any age group. Auditory PPI was less efficient in F344 rats than in LE rats. An age-related reduction of the PPI of ASR was observed in rats of both strains; however, a significant reduction of PPI occurred only in aged rats. The results indicate that the ASR may serve as an indicator of central presbycusis.
Keywords: předčasné stárnutí; Aging, Premature; druhová specificita; Auditory Threshold; Acoustic Stimulation; Female; Reflex, Acoustic; Reflex, Startle; stárnutí; krysa rodu Rattus; zvířata; Aging; Rats, Long-Evans; potkani inbrední F344; sluchový práh; úleková reakce; Rats, Inbred F344; ženské pohlaví; presbyakuze; Species Specificity; potkani Long-Evans; reflex akustický; Rats; Animals; Presbycusis; akustická stimulace